THE CONCEPT OF MARIA MONTESSORI IN EARLY CHILDHOOD EDUCATION (PAUD) - Maghfiroh, Muliatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Maria Montessori's educational concept exactly for Early Childhood Education and psychology. In the view of Maria Montessori, children not only build their own understanding of the world actively, but also their own understanding of discipline, or the ability to control and direct their focus and actions. Montessori said: "Childhood is the richest period, this time should be utilized by education as well as possible, if the wasted life of this era can never be searched instead. Our task is to utilize these early childhood years with the highest concern, rather than wasting it. Montessori education is based on the natural conditions of brain absorption and the spontaneous development of child sensitive periods to support physical and psychological development, and directs the child to health and freedom. Montessori learning environment for children aged 3 to 6 years is generally divided into four basic areas: first, practical life (daily life). Secondly, based on the senses (matter focuses on one or more senses). Third, the language. Fourth, math. In addition, music, art, movement and drama are also included in the curriculum. According to Montessori traditional education (old) a teacher who actively defines and imposes on the child everything that a child should do. In the Montessori school the teacher is just a leader, who observes the child to know the emergence of a student's sensitivity and then individual instruction. Once the child is attracted to his attention he is left active to find his own way. Teachers should always be objective in their view. And in the view of Montessori related learners of the present-day chest no one can teach the qualities that constitute the element of character formation. The only thing we can do is put education on a scientific basis, so children can work effectively, without being disturbed and hindered.